Egmont and Clärchen - Brend’amour, R. (Richard), 1831-1915 (engraver):::Creator::::::::::::; Hueberlin, C. (artist):::Contributor:::::::::::: (S. Hess)
Images of Egmont and Clara from Goethe's play Egmont